Study on Migration from conventional File System to advancement of Bigdata Technologies in the real world - Priyanka, P. Naga; Phaneendra, S. Vikram (International Journal of Computer Sciences and Engineering, 2014)
Now a day the internet was generating an explosion in growth of data in the form of data sets called Big Data that are complex to store, manage and analyze using conventional RDBMS that is used for Online Transaction Processing (OLTP) only. This new data is not only unstructured, voluminous but even more difficult to control, the cost of hardware and software infrastructure required to crunch it using conventional RDBMS. To exploit on the Big Data trend, a new type of Bigdata technologies (like Hadoop, HBase, PIG, HIVE, SQOOP,OOZIE, APACHE FLUME, MAHOUT) have developed by many companies that leverages new paralleled processing, commodity machines, open source framework to capture and analyze these new data sets. Bigdata presents a performance better than the existing Database or Data Warehouse or Business Intelligence systems. In this study we shall know how the emergent Bigdata is controlled for managing huge volume of data. This paper also lays out the ecosystem of big data technology that has been evolving rapidly.